Recently Discovered Urartian Cuneiform Inscriptions in the Temple of the Körzüt Fortress - Sabahattin Erdoğan; Anastasiia Süğlüm (Anadolu Araştırmaları)
This study examines the findings from the 2023 rescue excavations at the Körzüt Fortress in the Lake Van Basin. Three newly discovered cuneiform inscriptions offer significant evidence linking the fortress’s construction to the reign of the Urartian King Minua (810 - 786 BCE). The inscriptions recount the king’s victory over the Erkua tribe and the capture of the city of Luḫiuni. They detail the spoils brought to the Urartian capital, including men, women, horses, and livestock from the city and surrounding areas. This narrative underscores Körzüt’s strategic significance during Minua’s northern campaigns. Moreover, analysis indicates that inscriptions previously found nearby villages likely originated from this fortress. The excavation of the Susi Temple reveals a square-plan design characteristic of Urartian temple architecture, enhancing our understanding of the period’s religious and administrative structures. Collectively, these discoveries provide fresh insights into Urartu’s political and cultural organization and its broader regional influence. Körzüt Fortress has thus emerged as a critical center for the study of Urartian history and archaeology in the region.